The plot to kill God: findings from the Soviet experiment in secularization - Froese, Paul (University of California Press, 2008)
The great secularization experiment -- Dreams of secularization -- The atheist crusade -- Shutting off religious supply -- Hunting for religious demand -- After atheism -- The social and political resilience of God -- Notes -- Bibliography -- Index